Management of Infectious Pleurisies of Benin - BOGNON, GILLES; PADONOU, CAROLINE; ZOHOUN GUIDIBI, LUTECIA MYRIAME; ENIANLOKO HOUESSOU, NICOLE ZINHOUE (My University, 2022)
Objective: Infectious pleurisy is a frequent hospitalization indication in pediatrics in developing countries. This study aims to describe infectious pleurisies’ features and to identify its death factors in three teaching hospitals in Benin. Design: This was a prospective, descriptive and analytical study including children aged 01 months to 17 years who were hospitalized in pediatrics in the three hospitals for pleurisy from September to December 2019. Results: Among the 3379 children admitted, 25 presented with an infectious pleurisy, making a hospital frequency of 0.74%. The sex ratio was 0.8. The majority (19/25) of the children were less than 5 years old. The mean age was 38 ± 5.88 months. Most of the parents had a low education (42/50) and socio-economic status (18/25). The main symptoms were fever (25 cases), dyspnea (23 cases) and cough (22 cases). The majority of the children (21/25) were up-to-date in regards with the Expanded Immunization Program (EIP) vaccines and none had received non-EIP vaccines. Almost all children (24 cases) had a respiratory distress (24/25). On chest X-ray, there were abundant pleural extravasations in 12 cases. The main pathogens found were Staphylococcus aureus (16 cases), Streptococcus pneumoniae (3 cases) and Streptococcus A (1 case). All children received oxygen and antibiotic therapy; pleural drainage was performed in 22 children. The average length of stay was 14 days ± 6.4. Twenty-one children were healed without sequelae, one child had a post-drainage keloid scar, and two children died. Factors associated with the death of these children were admission delay for more than 7 days (p = 0.035) and presence of respiratory distress (p = 0.049). Conclusion: Pleurisy remains a concern for children admitted in our hospitals and early management is imperat
Keywords: Infectious Pleurisy; Respiratory Distress; Pleural Drainag